A risk-protective factors model of relapse and recovery among Filipinos with substance use disorder - Tuliao, Antover P. (2010)
The purpose of this study is to explore the reasons for relapse and recovery in Filipinos with substance use disorder. Because this study intended to be sensitive to recovery factors and ethnocultural nuances, a qualitative research paradigm was used with the grounded theory as the analytical lens. Relapse and recovery narratives from three recently relapsed and three abstaining individuals were gathered. A risk-protective factor was presented for both substance-use disorder relapse and recovery. The risk factor meta category is a collection of factors that increases the chances of relapse, viz.: psychiatric illness, negative affect, drug craving, and negative social environment. The protective factor meta category, on the other hand, refers to a group of variables that increases the probability of recovery, and it includes utilization of coping behaviors, motivation to change, vigilance, spirituality, and a positive social environment. The paper also discussed the interactions among the variables, implications for addiction counseling, and suggestions for future research.
Keywords: Substance abuse -- Relapse; Substance abuse -- Treatment